Wooden alphabet sign language as a way to interact and teach children - Olga V. Kaukina; Gelena A. Lavrichenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Today, inclusive education is being actively implemented in the process of teaching children with disabilities. One of the principles of inclusive education is the human right to communicate, the right to be unique, which reflect the ability to accelerate socialization through sign language. The paper deals with inclusive education in Europe and Russia. Definitions of inclusive education, sign language, and alphabet are given. A historical review of the education of children with hearing disabilities in different countries of Europe and Russia was conducted. This paper also highlights the results of studies in the field of inclusion, which were carried out by various scientific researchers and teachers. Based on the research of various scientists, the authors propose a model of the wooden sign alphabet as a visual didactic guide in the course of practical activities for better memorization of both the written and sign alphabet for children with disabilities. The goal of this project is to achieve a smooth transition from the study of sign language to the written alphabet.